A interferência das atividades antrópicas na qualidade da água em reservatório de abastecimento urbano. Estudo de caso: represa Dr. João Penido (Juiz de Fora, MG) - Bucci, Maria Magaly Heidenreich Silva; de Oliveira, Luiz Fernando Cappa (Eclética Química, 2014)
Dr. João Penido dam is the main reservoir for water supply of Juiz de Fora (MG). The forms of land use and occupation have produced negative impacts on the aquatic ecosystem. The general objective of this study was to assess the anthropogenic impact on water quality of the watershed. To this was done to characterize the quality of its waters and the parameters measured were compared with CONAMA Resolution 357/2005. It was also calculated the Water Quality Index (WQI) and the Trophic State Index (TSI). The monitoring tool has proved essential in actions involving preservation of the watershed.